The pacing landscape : comparison of relative power output in hypoxia and normoxia - Malterer, Katherine R. (My University, 2013)
Power output (PO) is systematically decreased at higher altitude; but, in air resisted activities the reduction in power losses to air friction is larger than the decreases in aerobic PO and result in a better performance (e.g. reduced time) at altitude. However, when comparing modeled races to actual world records, a performance deficit has been suggested. The purpose of this study was to determine if this underperformance could be attributable to a lower fractional utilization (average % PPO across the event) or errors of pacing strategy. Twelve healthy, well-trained cyclists performed two maximal incremental tests, two habituation trials, and two time trials (TT), one of each set in normoxia and one in hypoxia (FIO2 = 16%)( ~2300m). When PO was analyzed as a percent of peak power output (%PPO) from the maximal tests in each respective condition (hypoxic TT compared with hypoxic maximal test and normoxic TT with normoxic maximal test), %PPO at the beginning of the trial tended to be greater in hypoxia, and correspondingly lower late in the trial, but with no significant difference in the average fractional utilization. This suggests that cyclists may use a detrimentally high initial power output at altitude.
Keywords: Aerobic exercises--Physiological aspects.; Oxygen in the body.; Anoxemia.